Pultruded molded product and method for producing the same, and windmill blade
By using surface-treated inorganic fillers with controlled sedimentation and distribution, the resin scale issue in pull-out molding is mitigated, resulting in high-quality, low-pulling force composite materials.
Patent Information
- Application Number
- JP2023119658
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
Existing pull-out molding methods for fiber-enhanced composite materials face issues with resin scale formation due to resin residue, leading to surface defects and decreased productivity, and the distribution of inorganic fillers is inconsistent, affecting the suppression effect.
Incorporating surface-treated inorganic fillers with alcohoxylan compounds having epoxy, amino, or isocyanate groups, ensuring uniform distribution and slow sedimentation in the resin composition, with controlled particle size and density to minimize resin scale formation.
The method results in reduced resin scale and stable, low-pulling force production of composite materials with improved filler distribution, enhancing productivity and product quality.
Smart Images

Figure 2025016883000007 
Figure 2025016883000008 
Figure 2025016883000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a pultrusion product containing reinforcing fibers and a matrix resin, a method for producing the same, and a wind turbine blade including the pultrusion product as a structural member. [Background technology]
[0002] Fiber-reinforced composite materials, which consist of reinforcing fiber bundles such as carbon fiber and glass fiber and a matrix resin, are lightweight yet have excellent mechanical properties such as strength and rigidity, heat resistance, and corrosion resistance, and therefore have been applied to many fields such as aerospace, railway vehicles, ships, civil engineering and construction, and sporting goods.
[0003] As a method for producing a fiber-reinforced composite material, a method such as a prepreg method, a hand lay-up method, a filament winding method, a pultrusion method, an RTM (Resin Transfer Molding) method, etc. is appropriately selected and applied. Among them, the pultrusion method is a method that can relatively easily produce a fiber-reinforced composite material in which reinforcing fibers are aligned in one direction, and is excellent in cost performance.
[0004] In pultrusion molding, a residue of the cured resin, called "resin scale," accumulates in the mold. Resin scale occurs when the resin impregnated in the reinforcing fiber bundle is squeezed at the mold entrance, forming a resin-rich layer on the fiber surface, which then accumulates in the mold as a cured resin residue. Resin scale leads to problems such as a deterioration in the surface quality of pultrusion molded products and a decrease in productivity due to increased pulling force, so how to reduce resin scale is an issue.
[0005] Patent Document 1 discloses that inorganic fillers such as silicon compounds, magnesium compounds, and aluminum compounds are added to the resin used to form the pultrusion molded product, and it is said that the inorganic fillers penetrate between the fibers, thereby suppressing the hardening shrinkage of the resin and inhibiting the generation of resin scale. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 151174 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the technology of Patent Document 1 has the problem that the inorganic filler, which has a larger specific gravity than the resin, settles over time in the resin bath, which tends to cause variations in the distribution of the inorganic filler in the final pultrusion molded product, and therefore the effect of suppressing resin scale tends to be insufficient. [Means for solving the problem]
[0008] The present invention for solving the above problems is as follows. (1) A pultrusion molded product containing continuous reinforcing fiber bundles, a matrix resin, and an inorganic filler that has been surface-treated with an alkoxysilane compound having at least one group selected from an epoxy group, an amino group, and an isocyanate group. (2) The settling velocity ν of the inorganic filler calculated from Stokes' settling velocity equation (1) described later when the inorganic filler is uniformly dispersed in a resin composition corresponding to the state before the matrix resin is cured. s But 1.0×10 -10 cm / s or more 6.0×10 -8 The pultrusion molded product according to (1), wherein the pultrusion speed is equal to or less than cm / s. (3) The pultrusion molded product according to (2), wherein the viscosity of the resin composition at 25°C corresponding to the uncured state of the matrix resin is 1.0 Pa s or less. (4) The pultrusion molded article according to any one of (1) to (3), in which no aggregates of the inorganic filler having a maximum diameter of 50 μm or more are present in the matrix resin. (5) The pultrusion molded product according to any one of (1) to (4), wherein the content of the alkoxysilane compound is 0.5 parts by weight or more and 2.0 parts by weight or less with respect to 100 parts by weight of the inorganic filler. (6) The pultrusion molded product according to any one of (1) to (5), wherein the content of the inorganic filler is from 1 part by weight to 10 parts by weight based on 100 parts by weight of the matrix resin. (7) The pultrusion molded product according to any one of (1) to (6), wherein the matrix resin is selected from the group consisting of vinyl ester resins, epoxy resins, and polymethyl methacrylate resins. (8) The particle size of the inorganic filler is 10 μm or less, and the density is 2500 kg / m 3 The pultrusion molded product according to any one of (1) to (7) below: (9) The pultrusion molded product according to any one of (1) to (8), wherein the continuous reinforcing fiber bundles are carbon fiber bundles, and the volume content of the carbon fibers is 60% or more and 68% or less. (10) A method for producing a pultrusion molded product containing a continuous reinforcing fiber bundle, a matrix resin, and an inorganic filler, comprising the steps of: impregnating the continuous reinforcing fiber bundle in a resin bath with a resin composition before curing of the matrix resin, the resin composition including an inorganic filler that has been surface-treated with an alkoxysilane compound having at least one group selected from an epoxy group, an amino group, and an isocyanate group; A step of pulling out the continuous reinforcing fiber bundle from the mold while curing the resin composition in the mold; A method for producing a pultrusion molded product having the above structure. (11) In the resin composition in the resin bath, the sedimentation velocity ν of the inorganic filler calculated from the Stokes' sedimentation velocity equation (1) described below s But 1.0×10 -10 cm / s or more 6.0×10 -8 The method for producing a pultrusion molded product according to (10), wherein the pultrusion speed is 100.degree. (12) The method for producing a pultrusion molded product according to (10) or (11), wherein the viscosity of the resin composition in the resin bath is 1.0 Pa·s or less. (13) A wind turbine blade comprising, as a structural member, the pultrusion product according to any one of (1) to (9). Effect of the Invention
[0009] According to the present invention, there is provided a pultrusion molded product which generates little resin scale and can be produced with a stable low pulling force. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic diagram showing a pultrusion process. [Diagram 2] FIG. 2 is a schematic diagram showing an embodiment of a pultrusion molded product. [Diagram 3] 1 is a SEM image of the pultrusion molded product produced in Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present invention will be described in detail.
[0012] <Pultrusion method> FIG. 1 is a schematic diagram showing a manufacturing process 1 of a pultrusion molded product. The continuous reinforcing fiber bundle 2 set on the creel 3 is pulled out in one direction, passed through an eyelet guide, and then introduced into a resin bath 4 containing a liquid matrix resin composition, where the resin composition is impregnated. At this time, by dispersing an inorganic filler in the resin composition, the inorganic filler can be contained in the matrix resin of the pultrusion molded product. Thereafter, by passing through squeeze dies 5 and 6, the excess resin composition is squeezed out of the continuous reinforcing fiber bundle 2 impregnated with the resin composition so as to obtain a predetermined fiber content. Next, the continuous reinforcing fiber bundle 2 from which the excess resin composition has been squeezed out is introduced into a heated mold 7, and the matrix resin is cured by heating in the heated mold 7 to be molded. Then, the cured pultrusion molded product 9 is pulled out by a puller device 8, and wound into a coil by a winding device 10.
[0013] In this specification, the term "matrix resin" is used primarily to refer to the resin after curing in the pultrusion molded product, but may also refer to the resin composition before curing depending on the context. Also, the term "resin composition" basically refers to a liquid mixture of resin components that does not contain inorganic filler, but may also refer to a mixture that further contains inorganic filler depending on the context.
[0014] An embodiment of a pultrusion molded product 9 obtained by such a manufacturing process is shown in Figure 2. Figure 2A is a schematic diagram of a plan view of the pultrusion molded product 9, i.e., a view from above in Figure 1, and Figure 2B is a schematic diagram of a cross section perpendicular to the longitudinal direction of the pultrusion molded product 9. As shown in these figures, the pultrusion molded product 9 has a structure in which continuous reinforcing fiber bundles 2 are dispersed and arranged in a matrix resin 11. Although not shown, typically, in Figure 2, an inorganic filler is contained in a dispersed state in the matrix resin 11.
[0015] <Continuous reinforcing fiber bundle> Examples of fibers constituting the continuous reinforcing fiber bundles used in the pultrusion molded product of the present invention include carbon fibers, metal fibers, organic fibers, and inorganic fibers. Two or more of these may be used.
[0016] Examples of carbon fibers include polyacrylonitrile (PAN)-based carbon fibers made from PAN fibers, pitch-based carbon fibers made from petroleum tar or petroleum pitch, etc. Among these carbon fibers, PAN-based carbon fibers are preferably used because of their excellent balance between strength and elastic modulus.
[0017] In the pultrusion molded product, the reinforcing fibers are usually arranged in the form of one or more reinforcing fiber bundles each formed by bundling a large number of single fibers. When one or more reinforcing fiber bundles are arranged, the total number of filaments (single fibers) of the reinforcing fibers is preferably 1,000 to 2,000,000. From the viewpoint of productivity, the total number of filaments of the reinforcing fibers is more preferably 1,000 to 1,000,000, further preferably 1,000 to 600,000, and particularly preferably 1,000 to 300,000.
[0018] For applications requiring high strength, high rigidity and light weight, it is preferable to use carbon fiber bundles as the continuous reinforcing fiber bundles, and in this case, the carbon fiber content (volume content: Vf) is preferably 60% or more and 68% or less. The carbon fiber content in the pultrusion molded product of the present invention can be calculated by the method described in the examples below.
[0019] <Matrix resin> The matrix resin of the pultrusion molded product of the present invention may be either a thermosetting resin or a thermoplastic resin. In the case of a thermosetting resin, vinyl ester resin or epoxy resin is preferably used, and in the case of a thermoplastic resin, polymethyl methacrylate (PMMA) resin is preferably used.
[0020] Vinyl ester resin is a resin obtained by curing a resin composition obtained by dissolving and mixing a compound (vinyl ester) having a polymerizable unsaturated bond (double bond) generated by a ring-opening reaction (esterification) between a compound (epoxy resin) having a glycidyl group (epoxy group) and an unsaturated monocarboxylic acid such as (meth)acrylic acid, and a polymerizable monomer such as styrene.
[0021] Vinyl ester resin is cured by adding an organic peroxide, generating radicals through thermal decomposition of the organic peroxide, and then radically polymerizing the double bonds in the monomer and vinyl ester. It is also possible to use the energy of UV (ultraviolet) or visible light to decompose an initiator, generating radicals, and then causing a curing reaction of the resin.
[0022] As the epoxy resin, from the viewpoint of adhesiveness to the reinforcing fiber bundles, it is preferable to use an epoxy resin having a precursor such as a compound of a phenol, an amine, a carboxylic acid, or an intramolecularly unsaturated carbon.
[0023] Examples of glycidyl ether type epoxy resins having phenols as precursors include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, epoxy resins having a biphenyl skeleton, phenol novolac type epoxy resins, and cresol novolac type epoxy resins.
[0024] Examples of glycidylamine type epoxy resins using amines as precursors include tetraglycidyldiaminodiphenylmethane, glycidyl compounds of xylylenediamine, triglycidylaminophenol, and positional isomers of glycidylaniline, and alkyl or halogen-substituted products.
[0025] Examples of epoxy resins that have a carboxylic acid as a precursor include glycidyl compounds of phthalic acid, and various isomers of glycidyl compounds of hexahydrophthalic acid and dimer acid.
[0026] Examples of epoxy resins having an intramolecularly unsaturated carbon as a precursor include alicyclic epoxy resins.
[0027] The curing agent used for heat curing the epoxy resin may be an addition-reacting curing agent such as an amine or an acid anhydride, or may be a curing catalyst that induces addition polymerization such as cationic polymerization or anionic polymerization, or two or more types of curing agents may be used in combination. As the curing agent, a compound having an amino group, an acid anhydride group, or an azide group is preferably suitable. For example, phenolic compounds such as dicyandiamide, alicyclic amines, aliphatic amines, aromatic amines, aminobenzoic acid esters, various acid anhydrides, phenol novolac resins, cresol novolac resins, imidazole derivatives, and t-butylcatechol, as well as Lewis acid complexes such as boron trifluoride complexes and boron trichloride complexes, may be mentioned.
[0028] As the monomer raw material of PMMA resin, unsaturated carboxylic acid alkyl ester monomers are preferably used, specifically, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. can be mentioned.
[0029] Regarding the polymerization method of PMMA resin, basically, known methods such as radical bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. can be used, but solution polymerization, bulk polymerization, and suspension polymerization are particularly preferred in that they produce less impurities.
[0030] In order to reduce the pulling force during pultrusion molding, it is preferable to reduce the viscous resistance of the matrix resin composition in an uncured state in the mold. For this purpose, it is preferable to set the viscosity of the matrix resin composition before curing at 25°C to 1.0 Pa s or less. Note that the viscosity here means the complex viscosity measured by the method described in the Examples below.
[0031] <Inorganic filler> As the inorganic filler, fused silica, aluminum hydroxide, magnesium hydroxide, talc, kaolin and mica are preferably used.
[0032] The fused silica is made of a mineral called pegmatite, which is made of quartz, feldspar, and mica, and the quartz component is separated by flotation. The magnesium hydroxide is preferably a relatively pure magnesium hydroxide containing 80% by weight or more of an inorganic substance represented by the chemical formula Mg(OH)2. The talc is made of a layered mineral of hydrated magnesium silicate. The kaolin may be any of wet kaolin, calcined kaolin, and dry kaolin. The mica may be any of naturally occurring muscovite, biotite, phlogopite, and sericite, or artificially produced synthetic mica. The inorganic filler may be made of two or more of the above-mentioned materials.
[0033] The content of the inorganic filler in the pultrusion molded product of the present invention (i.e., the content of the inorganic filler in the resin composition before curing) is preferably 1 part by weight to 10 parts by weight, more preferably 3 parts by weight to 8 parts by weight, and even more preferably 4 parts by weight to 6 parts by weight. When the content of the inorganic filler is 1 part by weight to 10 parts by weight, the resin scale inhibition effect is easily and stably expressed.
[0034] In the present invention, the inorganic filler used is one that has been surface-treated with an alkoxysilane compound having at least one group selected from an epoxy group, an amino group, and an isocyanate group (hereinafter, sometimes simply referred to as an "alkoxysilane compound" in this specification), in other words, one that has an alkoxysilane compound attached to its surface. This improves the filler dispersion in the matrix resin in the resin bath during pultrusion molding, and the resin composition becomes uniform, thereby suppressing the generation of resin scale.
[0035] Specific examples of alkoxysilane compounds having an epoxy group include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxytriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0036] Specific examples of the alkoxysilane compound containing an amino group include γ-(2-aminoethyl)aminopropylmethyldimethoxysilane and γ-aminopropyltrimethoxysilane.
[0037] Specific examples of the alkoxysilane compound having an isocyanate group include γ-isocyanate propyl triethoxysilane, γ-isocyanate propyl ethyl dimethoxysilane, γ-isocyanate propyl ethyl dithoxysilane, and γ-isocyanate propyl trichlorosilane.
[0038] From the viewpoint of storage stability, as the alkoxysilane compound, an alkoxysilane compound having an epoxy group and an amino group is particularly preferably used.
[0039] The method for treating the surface of an inorganic filler with an alkoxysilane compound will be exemplified below.
[0040] A predetermined amount of the inorganic filler used in the present invention is placed in the container of a stirring device such as a Henschel mixer, and stirred at a given rotation speed for a certain period of time to break down aggregates, etc. Next, a spray gun containing a given amount of the alkoxysilane compound of the present invention is attached to the lid of the Henschel mixer, and surface treatment is performed by spraying with the spray gun while stirring at a given rotation speed.
[0041] The amount of the alkoxysilane compound is preferably 0.5 parts by weight or more and 2.0 parts by weight or less, more preferably 1.0 parts by weight or more and 1.8 parts by weight or less, relative to 100 parts by weight of the inorganic filler. By setting the amount in this range, the filler dispersibility in the resin bath is significantly improved, and the filler aggregation in the continuous reinforcing fiber bundle during impregnation is improved.
[0042] A preferred filler dispersion state in the matrix resin is a state in which there are no aggregates with a maximum diameter of 50 μm or more. In this specification, the filler dispersion state in the matrix resin is confirmed by scanning electron microscope (SEM) observation. Specifically, first, five points are randomly cut out from the pultrusion molded product so that the size is 20 mm wide x 20 mm long when viewed in plan, i.e., when viewed from above in FIG. 1, and embedded and polished to prepare a sample for observation. The embedding and polishing process here refers to setting an observation sample in a cylindrical ring of φ30 mm, injecting and embedding a room temperature fast-curing epoxy resin, and then completely curing the epoxy resin, and then setting a polishing disk on an automatic polishing device to polish the sample (guideline: surface roughness Ra = 0.05 μm). Next, the five samples are observed by SEM, and if no filler aggregates with a maximum diameter of 50 μm or more are observed, it is considered that no aggregates of the inorganic filler with a maximum diameter of 50 μm or more are present.
[0043] Figure 3 shows an image of the pultrusion molded product produced in Example 9, which will be described later, observed with an SEM. In Figure 3, the dashed circle indicated by 12 indicates the location of silica or its aggregates dispersed around the reinforcing fiber bundle. In this image, the maximum diameter of the silica aggregates is about 10 μm, and no aggregates with a maximum diameter of 50 μm or more are observed, which indicates that the silica is uniformly dispersed.
[0044] The sedimentation velocity ν of the inorganic filler in the present invention s The sedimentation velocity (cm / s) can be calculated using the Stokes equation (1) below.
[0045]
number
[0046] Dp: Particle diameter of inorganic filler (m) ρp: Density of inorganic filler (kg / m 3 ) ρf: Density of the resin composition at 25°C (kg / m 3 ) g:Gravity acceleration9.80665(m / s 2 ) η: Viscosity of the resin composition at 25°C (Pa s) The "resin composition" referred to here refers to a liquid matrix resin composition before curing that does not contain inorganic filler, and more specifically refers to a resin composition in a resin bath in an actual production process, or a resin composition before curing that is assumed from a cured matrix resin in a pultrusion molded product.
[0047] If the settling rate of the inorganic filler is slow, the settling of the inorganic filler in the resin bath in the pultrusion molding process is suppressed, the inorganic filler is more likely to be uniformly incorporated into the continuous reinforcing fiber bundle, and excessive resin squeezing at the mold inlet is alleviated. As a result, the resin-rich layer on the fiber bundle surface is reduced, and the generation of resin scale caused by the cured resin is suppressed.
[0048] Inorganic filler sedimentation velocity νs The preferred range is 1.0×10 -10 cm / s or more 6.0×10 -8 cm / s or less. s By setting the range, the filler settling property in the resin bath is significantly improved, the resin scale suppression effect is maximized, and a further reduction in the pull-out force can be expected. s If the viscosity is below this lower limit, the filler particles may easily pass through the gaps between the fiber bundles, and the resin scale suppression effect may be weakened.
[0049] In order to control the settling rate of the inorganic filler, it is preferable to optimize the particle size and density of the inorganic filler. The particle size of the inorganic filler is preferably 15 μm or less, and the filler density is preferably 2800 kg / m 3 Furthermore, the particle size is preferably 10 μm or less and the density is preferably 2500 kg / m 3 It is particularly preferable to use the following inorganic fillers. From the viewpoint of handling properties of the inorganic fillers, the particle size is 0.1 μm or more and the density is 2000 kg / m 3 In this specification, the particle size of the inorganic filler means the volume average particle size measured by the method described in the examples below.
[0050] The pultrusion product of the present invention can be suitably used as a structural member for a wind turbine blade, in particular as a structural member constituting a spar cap. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0052] 1.Various measurement methods [Resin viscosity at 25℃] 5 g of the matrix resin composition not containing the inorganic filler was weighed out and placed in a measuring jig (parallel plate). The complex viscosity was measured using a DMA device (model: ARES-G2 manufactured by TA Instruments) at 25°C for 5 minutes under a measurement strain of 10% and a frequency of 1.0 kHz.
[0053] [25℃ resin density] A 30 g sample of the matrix resin composition not containing the inorganic filler was transferred to a test tube and weighed on a floating balance (measurement range: 1000 to 1500 kg / m 3 The resin density was measured at 25°C, simulating the resin bath temperature.
[0054] [Particle size of inorganic filler] 100 mg of the raw inorganic filler shown in Tables 1 and 2 was weighed out and dispersed in water, and then the volume average particle diameter of the filler was measured using a laser diffraction / scattering type particle size distribution measuring device (LA-30 manufactured by HORIBA Corporation).
[0055] [Settling rate of inorganic filler] The filler settling velocity v s asked for.
[0056] 2. Evaluation method for pultrusion formability As evaluation indices for pultrusion formability, the following items were set and a simple evaluation was performed.
[0057] [Time when filler begins to settle in the resin bath] A pultrusion molding was produced by the manufacturing process shown in FIG. 1, and the settling of the filler in the resin bath 4 was visually observed during the production, and the time when the settling started was measured.
[0058] [Resin scale] Pultrusion molded products were manufactured using the manufacturing process shown in FIG. 1, and the state of resin scale generated in the mold 8 during the manufacturing process was visually inspected and the frequency of resin scale generation was evaluated according to the following criteria.
[0059] A: No resin scale occurs even after molding for 3 hours or more B: Resin scale occurs within 1 hour or more but less than 3 hours C: Resin scale appears in less than 1 hour [Pullout force] Pultrusion molded products were manufactured using the manufacturing process shown in FIG. 1. A load cell was installed in advance under the mold 8, and the pulling force 0.5 hours after the start of molding was evaluated according to the following criteria.
[0060] S: Pulling force less than 100 kg A: Pull-out force: 100kg or more and less than 300kg B: Pull-out force: 300kg or more and less than 1000kg C: Pulling force 1000kg or more [Appearance of molded product] The appearance of the molded product obtained by the manufacturing process shown in Figure 1 was judged according to the following criteria.
[0061] A: Good appearance of molded product B: There are scratches on the surface of the molded product. C: There are chips on the edge of the molded product or scratches on the surface. 3. Evaluation method for pultrusion molded products [CF volume content (Vf)] After measuring the mass W0 of the pultrusion molded product, the pultrusion molded product was heated in air at 550 ° C. for 240 minutes to burn off the resin components, the mass W1 of the remaining reinforcing fibers was measured, and the CF volume content (Vf) of the pultrusion molded product was calculated by the following formula.
[0062] Vf (volume%) = (W1 / ρf) / {W1 / ρf+(W0-W1) / ρ1}×100 ρf: Density of reinforcing fiber (g / cm 3 ) [Mechanical property evaluation] (1) Bending test (0° direction: reinforcing fiber bundle direction in plan view) The pultrusion molded products obtained in Tables 1 and 2 were cut with an autocutter to a width of 15 mm, length of 250 mm, and thickness of 5 mm with the 0° direction as the length direction to obtain 0° direction bending test pieces. Next, bending tests were performed with N=5 using an Instron 5565 device in a three-point bending mode (indenter diameter: upper φ10, lower φ4) with a crosshead speed of 12 mm / min and a span distance of 190 mm.
[0063] (2) Bending test (90° direction: direction perpendicular to the reinforcing fiber bundle direction in plan view) The pultrusion molded products obtained in Tables 1 and 2 were cut with an autocutter to a width of 15 mm, length of 50 mm, and thickness of 5 mm with the 90° direction as the length direction, to obtain 90° bending test pieces. Next, bending tests were performed with N=5 using an Instron 5565 device in a three-point bending mode (indenter diameter: upper φ10, lower φ4) with a crosshead speed of 1 mm / min and a span distance of 40 mm.
[0064] (3) Interlaminar shear strength test (ILSS) The pultrusion molded product was cut with an autocutter to a width of 10 mm, length of 35 mm, and thickness of 5 mm with the 0° direction as the length direction to obtain a 0° direction interlaminar shear strength test piece. Next, a bending test was performed with N=5 using an Instron 5565 device in a three-point bending mode (indenter diameter: upper φ10, lower φ4) with a crosshead speed of 1 mm / min and a span distance of 25 mm.
[0065] 4. Manufacturing method of pultrusion molded products [Raw materials] (1) Matrix resin composition <Thermosetting-1> Base material: Bisphenol A vinyl ester resin, DIC pultrusion grade, "EPICLON (registered trademark) UE-3505" Initiator 1: t-butyl peroxy-2-ethylhexanoate, a radical initiator manufactured by Nouryon Chemical Industries, "Trigonox (registered trademark) 21-50E" Initiator 2: t-butyl peroxybenzoate, a radical initiator manufactured by Nouryon Chemical Industries, "Trigonox (registered trademark) C" <Thermosetting-2> Base resin: Bisphenol A type epoxy resin, Huntsman pultrusion grade, "ARALDITE (registered trademark) LY3585" Hardener: Tetrahydromethylphthalic anhydride, Huntsman hardener, "ARADUR® 917-1" Curing catalyst: Imidazole compound, Huntsman curing catalyst, "ACCELERATOR (registered trademark) DY080" <Thermoplastic-1> Base material: MMA monomer, Arkema pultrusion grade, "Elium (registered trademark) C595-E" Initiator 1: Di(4-butylcyclohexyl)peroxydicarbonate, a radical initiator manufactured by Nouryon Chemical Industries, "Perkadox (registered trademark) 16" Initiator 2: t-butyl peroxybenzoate, a radical initiator manufactured by Nouryon Chemical Industries, "Trigonox (registered trademark) C" (2) Inorganic filler Aluminum hydroxide-1: Volume average particle size 1.5 μm, density: 2.42 g / cm 3 Aluminum hydroxide-2: Volume average particle size 10 μm, density: 2.42 g / cm 3 Aluminum hydroxide-3: Volume average particle size 0.5 μm, density: 2.42 g / cm 3 Aluminum hydroxide 4: average particle size 15 μm, density: 2.42 g / cm 3 Talc-1: Volume average particle size 1.5 μm, density 2.82 g / cm 3 Talc-2: Volume average particle size 10 μm, density 2.82 g / cm 3 Silica-1: Volume average particle size 1.5 μm, density 2.60 g / cm 3 Silica-2: Volume average particle size 15 μm, density 2.60 g / cm 3 Kaolin-1: Volume average particle size 1.5 μm, density 2.60 g / cm 3 Kaolin-2: Volume average particle size 15 μm, density 2.60 g / cm 3 Mica-1: Volume average particle size 5 μm, density 2.80 g / cm 3 Mica-2: Volume average particle size 15 μm, density 2.80 g / cm 3 (3) Alkoxysilane compounds KBM303: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, Shin-Etsu Silicone Silane Coupling Agent, KBM903: 3-aminopropyltrimethoxysilane, a silane coupling agent manufactured by Shin-Etsu Silicones KBE9007: 3-isocyanatopropyltriethoxysilane, a silane coupling agent manufactured by Shin-Etsu Silicones Co., Ltd. Carbon fiber: "TORAYCA (registered trademark)" T700S-24K (24,000 filaments, manufactured by Toray Industries, Inc.) [Surface treatment method for inorganic filler] 5 kg of inorganic filler shown in Tables 1 and 2 was charged into a 10 L capacity Henschel mixer body (manufactured by Nippon Coke & Engineering Co., Ltd., model FM10) and stirred at a rotation speed of 20 m / s for 10 to 15 minutes to break down filler aggregates. Next, a spray gun charged with 250 g of an alkoxysilane compound shown in Tables 1 and 2 was set on the lid of the Henschel mixer, and the filler surface was treated by spraying with the spray gun at a rotation speed of 40 m / s. The amount of the alkoxysilane compound used for surface treatment was 1.0 part by weight of the alkoxysilane compound per 100 parts by weight of the filler. The shape of the Henschel mixer stirring blade was the standard type of Nippon Coke & Engineering Co., Ltd. (compatible with model FM10: two-piece set of upper blade / lower blade).
[0066] [Method of preparing matrix resin composition for pultrusion molding] The raw materials (resin composition, inorganic filler) shown in Tables 1 to 3 were charged in a 5 L disposable cup container so as to have a prescribed mixing ratio, and stirred with a stainless steel stirring blade at 700 rpm for 60 minutes.
[0067] A pultrusion molded product was manufactured by the manufacturing process shown in FIG. 1 using the resin composition containing the inorganic filler prepared in this way. A pultrusion mold having a width of 50 mm, a length of 750 mm, and a thickness of 5.2 mm was used, and the CF bobbin was set in the creel 3 of FIG. 1 so that the CF content (volume content: Vf) was 62%. As shown in FIG. 1, the resin composition was put into a resin bath 4 whose temperature was adjusted to 25°C, and the carbon fiber bundle (continuous reinforcing fiber bundle 2) was passed through it to be impregnated with the resin. Next, the resin-impregnated fiber base material 7 from which excess resin was squeezed out when passing through the squeeze bars 5 and 6 was introduced from the inlet of the mold 8 and continuously cured, and the pultrusion molded product coming out of the outlet of the mold 8 was collected in a coil shape by the winding device 10 at the take-up speeds of 0.2 m / min and 0.4 m / min of the puller device 9. The mold temperature was set as follows depending on the resin type of the resin composition. Heat curing - 1: mold inlet 120℃, mold center 160℃, mold outlet 150℃ Heat curing 2: Mold entrance 120℃, mold center 160℃, mold exit 150℃ Thermoplasticity-1: Mold entrance 90℃, mold center 110℃, mold exit 100℃
[0068] [Table 1]
[0069] [Table 2]
[0070] [Table 3] [Explanation of symbols]
[0071] 1. Manufacturing process of pultrusion products 2 Continuous reinforcing fiber bundle 3 Creel 4 Resin Bath 5, 6 Squeeze Bar 7 Pultrusion mold 8 Puller device 9 Pultrusion products 10 Winding device 11 Matrix resin 12 Dashed circle indicating location of silica or silica aggregates
Claims
1. A pultrusion molded article comprising a continuous reinforcing fiber bundle, a matrix resin, and an inorganic filler that has been surface-treated with an alkoxysilane compound having at least one group selected from an epoxy group, an amino group, and an isocyanate group.
2. The settling velocity ν of the inorganic filler calculated from the following Stokes' settling velocity equation (1) when the inorganic filler is uniformly dispersed in a resin composition corresponding to the state before the matrix resin is cured. s But 1.0 x 10 -10 cm / s or more 6.0×10 -8 The pultrusion molded product according to claim 1, wherein the pultrusion speed is 100 mm / s or less. [0010] Dp: Particle diameter of inorganic filler (m) ρp: Density of inorganic filler (kg / m 3 ) ρf: density of the resin composition at 25 ° C. (kg / m 3 ) g: Gravitational acceleration 9.80665 (m / s 2 ) η: Viscosity of the resin composition at 25 ° C. (Pa s)
3. 3. The pultrusion molded product according to claim 2, wherein the viscosity of the resin composition corresponding to the uncured state of the matrix resin at 25°C is 1.0 Pa·s or less.
4. The pultrusion molded product according to any one of claims 1 to 3, wherein the matrix resin does not contain aggregates of the inorganic filler having a maximum diameter of 50 µm or more.
5. The pultrusion molded product according to any one of claims 1 to 3, wherein the content of the alkoxysilane compound is 0.5 parts by weight or more and 2.0 parts by weight or less with respect to 100 parts by weight of the inorganic filler.
6. The pultrusion molded product according to any one of claims 1 to 3, wherein the content of the inorganic filler is 1 part by weight or more and 10 parts by weight or less with respect to 100 parts by weight of the matrix resin.
7. The pultrusion molded article according to any one of claims 1 to 3, wherein the matrix resin is selected from the group consisting of vinyl ester resins, epoxy resins, and polymethyl methacrylate resins.
8. The inorganic filler has a particle size of 10 μm or less and a density of 2500 kg / m 3 The pultrusion molded product according to any one of claims 1 to 3, wherein:
9. The pultrusion molded product according to any one of claims 1 to 3, wherein the continuous reinforcing fiber bundle is a carbon fiber bundle, and the volume content of the carbon fiber is 60% or more and 68% or less.
10. A method for producing a pultrusion molded product containing a continuous reinforcing fiber bundle, a matrix resin, and an inorganic filler, comprising the steps of: impregnating the continuous reinforcing fiber bundle in a resin bath with a resin composition before curing of the matrix resin, the resin composition including an inorganic filler that has been surface-treated with an alkoxysilane compound having at least one group selected from an epoxy group, an amino group, and an isocyanate group; A step of pulling out the continuous reinforcing fiber bundle from the mold while curing the resin composition in the mold; A method for producing a pultrusion molded product having the above structure.
11. In the resin composition in the resin bath, the sedimentation velocity ν of the inorganic filler calculated from the following Stokes' sedimentation velocity equation (1) s But 1.0 x 10 -10 cm / s or more 6.0×10 -8 The method for producing a pultrusion molded product according to claim 10, wherein the pultrusion speed is 100 cm / s or less. [0025] Dp: Particle diameter of inorganic filler (m) ρp: Density of inorganic filler (kg / m 3 ) ρf: density of the resin composition at 25 ° C. (kg / m 3 ) g: Gravitational acceleration 9.80665 (m / s 2 ) η: Viscosity of the resin composition at 25 ° C. (Pa s)
12. The method for producing a pultrusion molded product according to claim 9 or 10, wherein the viscosity of the resin composition in the resin bath is 1.0 Pa·s or less.
13. A wind turbine blade comprising the pultrusion product according to any one of claims 1 to 9 as a structural member.
Citation Information
Patent Citations
Fiber-reinforced molded article and method for producing same
WO2019151174A1